Chronic migraine in women is associated with insulin resistance: a cross‐sectional study. (15th November 2013) - Fava, A.; Pirritano, D.; Consoli, D.; Plastino, M.; Casalinuovo, F.; Cristofaro, S.; Colica, C.; Ermio, C.; De, M.; Opipari, C.; Lanzo, R.; Consoli, A.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Migraine is a common neurological disorder. It can be divided into episodic migraine (EM) and chronic migraine (CM), based on headache frequency. Some studies have shown that insulin sensitivity is impaired in migraine; moreover, hypertension, diabetes and obesity are common in patients with CM. The aim of this study was to assess serum glucose, insulin levels and insulin resistance (IR) in a sample of episodic migraineurs, chronic migraineurs and non‐pain healthy controls. Methods Eighty‐three women with EM, 83 with CM and 83 healthy controls were recruited. Headache was diagnosed according to the latest International Classification of Headache Disorders 2 criteria. Waist circumference, body mass index (BMI) and blood pressure were measured. Checked metabolic parameters included fasting glucose, the 2 h 75 g oral glucose tolerance test (2 h OGTT), serum HbA1c, blood lipid profile, C‐reactive protein and prolactin. The homeostasis model assessment formula was used to calculate IR. Results A significant prevalence of IR in CM was observed (P = 0.002). No significant associations were found with fasting glycaemia, the 2 h OGTT, HbA1c, blood lipid profile, C‐reactive protein, prolactin and waist circumference. Obesity (BMI >30 kg/m2) was associated with an increased risk of CM [odds ratio (OR) 2.4]. When the outcome of interest was the association between IR and obesity, the OR was significantly increased compared with IR alone (OR = 13.2). Conclusion This may suggest that CM is associated with IR status, particularly when it is in partnership with obesity.